Ecological intensification decreased yield-scaled N20 emissions in a soybean-barley- maize sequence = La intensificación ecológica redujo las emisiones de N2O a escala de rendimiento en una secuencia de soja-cebada-maíz - Casanave Ponti, Sheila Mailén; Videla, Cecilia del Carmen; Rizzalli, Roberto Héctor; Monterubbianesi, María Gloria; García, Fernando Oscar; Ortega, Facundo Miguel; Andrade, Fernando Hector (Asociación Argentina de la Ciencia del Suelo, 2023)
Agricultural challenge today is to maximize crop production reducing negative environmental impacts by efficiently use of resources and inputs. Objectives: i) to evaluate N2O emissions during a soybean-barley-maize rotation and their respective interperiods -chemical fallows (ChF) and cover crops (CC)-, and ii) to understand the relationships between N2O flow rates with soil mineral N content (Nmin), water-filled porous space (WFPS), and soil temperature (ST). N2O emissions were evaluated weekly under two management systems, ecological intensification (EI) and farmer current practices (FP). EI included higher N rates than FP, split N application, a cover crop (CC) after barley, among other management practices. Simultaneously to N2O emissions, Nmin, WFPS and ST were determined. The N2O fluxes were highest during crop periods (9-43, 6-61 and 4-104 μg N2O-N m-2 h-1, for soybean, barley and maize, respectively), intermediate during barley-maize interperiod (2-47 and 3-35 μg N2O-N m-2 h-1, for CC and ChF, respectively) and lowest during ChF of maize-soybean and soybean-barley interperiods (1-26 and 5-22 μg N2O-N m-2 h-1, respectively). Regression tree provided threshold splits for the effect of soil variables on emission rates: 7.4 mg N kg-1 for Nmin; 10.35 or 8.7°C for ST, depending on Nmin and WPFS values; 39.6 and 55.4 % for WPFS, both with high N. There were no significant differences in accumulated N2O emissions between management systems for the complete sequence (3050 and 3380 g N2O-N ha-1, for EI and FP, respectively). Yield-based N2O emissions for the complete sequence were lower for EI than for FP. EI decreased yield-scaled N2O emissions by 29% for soybean (p<0.05) and barley (ns) and by 30% for maize (p<0.05) compared with FP. In conclusion for the complete sequence, the EI system did not increase N2O emissions per unit area and reduced emissions per unit yield despite utilizing higher N rates and including a CC.